Comparative Analysis of Physiological, Enzymatic, and Transcriptomic Responses Revealed Mechanisms of Salt Tolerance and Recovery in Tritipyrum - Peng, Ze; Wang, Yiqin; Geng, Guangdong; Yang, Rui; Yang, Zhifen; Yang, Chunmiao; Xu, Ruhong; Zhang, Qingqin; Kakar, Kaleem U.; Li, Zhenhua; Zhang, Suqin (Frontiers in Plant Science, 2022)
Salt stress results in the severe decline of yield and quality in wheat. In the present study, salt-tolerant Tritipyrum (‘Y1805’) and salt-sensitive wheat ‘Chinese Spring’ (‘CS’) were selected from 121 wheat germplasms to test their physiological, antioxidant enzyme, and transcriptomic responses and mechanisms against salt stress and recovery. 56 chromosomes were identified in ‘Y1805’ that comprised A, B, and D chromosomes from wheat parent and E chromosomes from Thinopyrum elongatum, adding to salt-tolerant trait. Salt stress had a greater inhibitory effect on roots than on shoots, and ‘Y1805’ demonstrated stronger salt tolerance than ‘CS’. Compared with ‘CS’, the activities of superoxide dismutase and catalase in ‘Y1805’ significantly increased under salt stress. ‘Y1805’ could synthesize more proline and soluble sugars than ‘CS’. Both the net photosynthetic rate and chlorophyll a/b were affected by salt stress, though the level of damage in ‘Y1805’ was significantly less than in ‘CS’. Transcriptome analysis showed that the differences in the transcriptional regulatory networks of ‘Y1805’ were not only in response to salt stress but also in recovery. The functions of many salt-responsive differentially expressed genes were correlated closely with the pathways ‘peroxisome’, ‘arginine and proline metabolism’, ‘starch and sucrose metabolism’, ‘chlorophyll and porphyrin metabolism’, and ‘photosynthesis’.